MOVING EDUCATIONAL ROLE-PLAY BEYOND ENTERTAINMENT - Thomas Duus Henriksen (Ediciones Universidad de Salamanca, 2010)
Educational role-play has long proved an effective tool for consultants trying to develop the skills that employees are using for performing certain job functions. However, while educational role-play often is presented as an entertaining means for learning, such insistence on making learning games more gamish seems to have an inhibiting effect on designing and thinking games beyond mere skill acquisition. By emphasising the role-play based process as a conflictual negotiation between distinctive categories of knowledge, this paper presents the explorative application of knowledge, while framing the facilitation of reflective processes as the key for transcending knowledge from the game's context to that of the participants. While pointing towards the compatibility issues between current conceptions of learning games and the facilitation of reflective processes, the paper emphasises the need for thinking the learning game as a part of a didactic design, rather than something beneficial in itself.